France - Bayle, E.; Durand, C.; Scelles, N. (Comparative elite sport development. Systems, structures and public policy, 2025)
France is western Europe's largest country. Including its numerous overseas territories across all five continents, it covers an area of 672,051 km2. On January 1, 2022, it was home to 68 million people, approximately 20% of whom are immigrants from outside Europe, a legacy of the country's colonial past. Politically, the French Republic is a secular liberal democracy. Although it is only the world's seventh-largest economy, France is an important player in the world's social, economic, political, cultural, and sporting decision-making bodies. France now owes much of its global influence to its membership of the European Union, of which it was one of the founding members. It also exerts influence through the French language, which is spoken by 220 million people around the world (Government, n.d.).